Analysis of transforming activity of human synovial sarcoma-associated chimeric protein SYT-SSX1 bound to chromatin remodeling factor hBRM/hSNF2α - Nagai, Makoto (The National Academy of Sciences, 2001)
Human synovial sarcoma has been shown to exclusively harbor the chromosomal translocation t(X;18) that produces the chimeric gene SYT-SSX. However, the role of SYT-SSX in cellular transformation remains unclear. In this study, we have established 3Y1 rat fibroblast cell lines that constitutively express SYT, SSX1, and SYT-SSX1 and found that SYT-SSX1 promoted growth rate in culture, anchorage-independent growth in soft agar, and tumor formation in nude mice. Deletion of the N-terminal 181 amino acids of SYT-SSX1 caused loss of its transforming activity. Furthermore, association of SYT-SSX1 with the chromatin remodeling factor hBRM/hSNF2α, which regulates transcription, was demonstrated in both SYT-SSX1-expressing 3Y1 cells and in the human synovial sarcoma cell line HS-SY-II. The binding region between the two molecules was shown to reside within the N-terminal 181 amino acids stretch (aa 1–181) of SYT-SSX1 and 50 amino acids (aa 156–205) of hBRM/hSNF2α and we found that the overexpression of this binding region of hBRM/hSNF2α significantly suppressed the anchorage-independent growth of SYT-SSX1-expressing 3Y1 cells. To analyze the transcriptional regulation by SYT-SSX1, we established conditional expression system of SYT-SSX1 and examined the gene expression profiles. The down-regulation of potential tumor suppressor DCC was observed among 1,176 genes analyzed by microarray analysis, and semi-quantitative reverse transcription–PCR confirmed this finding. These data clearly demonstrate transforming activity of human oncogene SYT-SSX1 and also involvement of chromatin remodeling factor hBRM/hSNF2α in human cancer.